2018
DOI: 10.1002/jcc.25709
|View full text |Cite
|
Sign up to set email alerts
|

Polarizable force field for RNA based on the classical drude oscillator

Abstract: RNA molecules are highly dynamic and capable of adopting a wide range of complex, folded structures. The factors driving the folding and dynamics of these structures are dependent upon a balance of base pairing, hydration, base stacking, ion interactions, and the conformational sampling of the 2’-hydroxyl group in the ribose sugar. The representation of these features is a challenge for empirical force fields used in molecular dynamics simulations. Towards meeting this challenge, the inclusion of explicit elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 112 publications
2
70
0
Order By: Relevance
“…Radical approach to overcome the limitations is the ongoing development of more sophisticated polarizable ffs. [5][6][7][8][9] Alternatively, we have suggested that improvements could be achieved also by extending the pair-additive ffs by new simple terms that are uncoupled from the existing ff terms and thus allow tuning of simulations of problematic systems while minimizing undesirable side effects. We have introduced an additional ff term called HBfix (H-bond fix), 10 that can be used to tune the description of key hydrogen-bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Radical approach to overcome the limitations is the ongoing development of more sophisticated polarizable ffs. [5][6][7][8][9] Alternatively, we have suggested that improvements could be achieved also by extending the pair-additive ffs by new simple terms that are uncoupled from the existing ff terms and thus allow tuning of simulations of problematic systems while minimizing undesirable side effects. We have introduced an additional ff term called HBfix (H-bond fix), 10 that can be used to tune the description of key hydrogen-bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A radical solution of the RNA ff problem could be the use of polarizable ffs. [18][19] However, their sophisticated parametrization not only results in extra computational cost but it yet remains to be seen if their accuracy will eventually surpass the best non-polarizable RNA ffs in extended simulations. Another option is to augment the existing ff forms by some additional simple ff terms that could be used to tune the ff performance while minimizing adverse side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Our data could serve as an important guidance for tuning of pair-additive as well as polarizable ffs. 92,93 However, when trying to design ff corrections based on this knowledge, we still could not get a decisive improvement. There could be several reasons for this.…”
Section: Discussionmentioning
confidence: 99%